Characterization of the dielectric properties of biological tissues using mixture equations and correlations to different states of hydration. (28th March 2019) - Pollacco, D A; Farrugia, L; Conti, M Caligari; Farina, L; Schembri Wismayer, P; Sammut, C V
Abstract: The aim of this study was to characterize the hydration fractions of biological tissues and to model these accurately from mixture equations. Hydration fractions, better known as volume fractions, are based on quantification of tissue hydration and accurate knowledge about the physiological composition of tissue fluids. Data on weight loss percentages for excised muscle and adipose tissue from a previous study were utilized for this purpose. The Bruggeman and Maxwell Garnett equations were then used to characterize the dielectric properties of the tissues in terms of mixtures of dry biological constituents and physiological saline solutions. It is shown that these models are accurate in modelling in vivo and ex vivo tissue in different states of hydration. This is based on precise knowledge of the physiological composition of biological fluids and their corresponding percentage contents.